Studies on the production of beef from zebu cattle in East Africa II. Milk production in suckled cows and its effect on calf growth - Lampkin, K.M.; Lampkin, G.H. (Cambridge University Press, 1960)
Productivity of zebu cows was investigated. Estimation of milk quantity obtained by calves, and effect of milk production on calf growth and live weight of suckled zebu cows were examined.